Study of the Working and Organisation of the Agriculture Division - Planning Commission (Planning Commission, Government of India, 1969)
The Telecommunications Capacity Planning Committee Report (May 1973) provides a strategic framework for the development and expansion of India’s telecommunications infrastructure during the 5th and 6th Five-Year Plans. The report identifies a significant gap between growing demand and indigenous manufacturing capacity, citing a waiting list of 3.4 lakh telephone applicants as of 1972 and highlighting low telephone density. It emphasizes the financial profitability of telecommunications and the urgency of establishing local production facilities for switching equipment, transmission systems, coaxial cables, microwave antennas, and related components to reduce import dependence. The plan outlines phased factory expansions, including the establishment of additional production units by 1978-79 and capacity enhancements for power plants, batteries, and testing instruments. It advocates for subcontracting, specialization of public sector units, and increased R&D investment to ensure efficient production. Projected investments of ₹125–190 crores are justified by high returns and potential export opportunities. Additionally, the report highlights the need to introduce new services such as high-speed data transmission, facsimile communication, and mobile telephony to meet future user demands. A standing committee is recommended to monitor demand, production, and technological advancements, ensuring responsive and timely infrastructure development. Overall, the report underscores the importance of proactive planning, timely investment, and indigenous capacity building to create a self-reliant and modern telecommunications ecosystem in India.
Management and Project Evaluation Division, Committee On Plan Projects, Planning Commission March, 1969
Keywords: Telecommunications Infrastructure; Capacity Planning; Indigenous Manufacturing; Telephone Demand; Investment Requirements; Switching Equipment; Transmission Equipment; Microwave Technology; Five-Year Plans; R&D; Export Potential; Mobile Communication